2005
DOI: 10.1111/j.1600-0501.2005.01125.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical advantages with ITI TE® implants placement in conjunction with split crest technique

Abstract: Implant rehabilitation of the edentulous maxilla may be somewhat problematic because of anatomic situations involving insufficient bone thickness. One approach in this situation is localized ridge augmentation with the split crest technique. This surgical approach allows the external cortical plate of the maxilla to be moved in a labial direction to gain an increase in width to introduce implants of appropriate diameter. This ongoing prospective study evaluated: (i) the surgical advantages that the new ITI TE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 27 publications
(58 reference statements)
5
48
0
2
Order By: Relevance
“…As regards the ridge expansion effect of AOT, the amount of horizontal bone gain was smaller than that reported in other studies, where ERE was achieved by means of original ERE (3.5 mm), [50] the split-crest technique with ultrasonic bone surgery (2.8 mm), [22] the split-crest technique plus autogenous bone and graft biomaterial (4.8 mm), [51] the extension-crest device (3.9 mm) [52] or the two-stage split-crest technique (7.1 mm). [23,53] However, AOT reduces the risk of intraoperative complications, such as cortical plate fractures, and makes it easier to prepare an adequate implant site without the use of split-thickness flaps, sagittal osteotomy and graft biomaterials.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…As regards the ridge expansion effect of AOT, the amount of horizontal bone gain was smaller than that reported in other studies, where ERE was achieved by means of original ERE (3.5 mm), [50] the split-crest technique with ultrasonic bone surgery (2.8 mm), [22] the split-crest technique plus autogenous bone and graft biomaterial (4.8 mm), [51] the extension-crest device (3.9 mm) [52] or the two-stage split-crest technique (7.1 mm). [23,53] However, AOT reduces the risk of intraoperative complications, such as cortical plate fractures, and makes it easier to prepare an adequate implant site without the use of split-thickness flaps, sagittal osteotomy and graft biomaterials.…”
Section: Resultsmentioning
confidence: 56%
“…Ferrigno and Laureti [51] proposed a novel implant design in order to reduce the risk of fracture of the labial cortical plate during the last two steps of the split-crest technique: (1) implant site preparation and (2) implant insertion. Nevertheless, the authors observed that buccal plate fracture occurred in 5% of cases, in which removal of the cortical plate was required in order to perform a GBR technique with minced autogenous bone plus graft biomaterials.…”
Section: Resultsmentioning
confidence: 99%
“…High survival and success rates (90.7-100%) for the two systems have been individually reported in many earlier studies [24][25][26][27][28][29][30][31][32][33][34][35][36][37] . Regarding the Br In this retrospective article, most cases had been applied a delayed loading after the placement of implant.…”
Section: Discussionmentioning
confidence: 93%
“…In fourteen studies, gap filling for all subjects was done, while in 4 cases selective gap filling was done. Gap filling may or may not influence the final outcome of implant success [24, 25] however, since the graft material takes part in the bone remodelling process, it expedites the healing process. Ella et al [26] advocated the use of bone filling substitutes, especially in the horizontally expanded sites as it resulted in reduced resorption around the implant bony walls.…”
Section: Resultsmentioning
confidence: 99%